Challenges Faced By Female Counselors in Providing HIV Testing and Counseling Services in Kashmir: A Qualitative Interpretive Inquiry - Mariya Amin Qurieshi; Inaamul Haq; Khalid Bashir; S. Mohammad Salim Khan; Samir Mattoo; Irfan Farooq Bhat; Imran Ahmad Rather (Indian Journal of Public Health)
Background: India’s adult HIV prevalence (15–49 years) has declined from 0.54% in 2000–2001 to 0.22%. Female HIV counselors encounter significant challenges, particularly given the cultural sensitivities around discussing sexual health. Objectives: To explore the lived experiences of female HIV counselors in Kashmir in providing HIV counseling. To examine the latent and manifest challenges embedded in providing counseling to HIV-positive patients. Materials and Methods: This qualitative study employed interpretative phenomenological analysis (IPA). In-depth interviews were conducted with 11 female HIV counselors working in Integrated Counseling and Testing Centers across Kashmir from December 2022 to January 2023. One interview with a counselor from Leh was conducted via Zoom. Data were transcribed and analyzed using IPA to identify the key themes. Results: The data analysis revealed a lack of institutional support, inadequate counseling spaces, and skepticism about counseling effectiveness. Most HIV counselors (81%) reported insufficient support from hospital authorities, and 72% experienced breaches in patient confidentiality, highlighting a lack of supervision and administrative backing. In addition, 90% indicated that counseling spaces lacked privacy, compromising the quality of sessions, (63%) expressed doubts about the effectiveness of their counseling due to heavy workloads and limited time. Conclusion: Female HIV counselors in Kashmir face various challenges, including a lack of privacy, workforce, supervision, and support from hospital administration. Additional issues include inadequate training, particularly in counseling substance users, insufficient HIV sensitization training for healthcare professionals, and dissatisfying salaries. Addressing these factors is essential for improving the efficacy of HIV counseling services in the region.